FACTORS INFLUENCING ACCOUNTING FRAUD TENDENCIES IN VILLAGE CREDIT INSTITUTIONS (LPDs) IN DENPASAR CITY - I Gede Bagus Windu Yoga Ananda; I Wayan Suartana (Adisam Publisher, 2026)
Accounting fraud is an intentional act committed to mislead other parties through the manipulation of financial statements, concealment of information, or misappropriation of organizational assets for personal gain. This practice can threaten the sustainability of financial institutions, including Village Credit Institutions (Lembaga Perkreditan Desa/LPD). The successful financial performance of LPDs in Denpasar City has created a dualism of perspectives, namely as the result of effective internal control systems that are able to reduce the risk of accounting fraud or as an indication of the existence of accounting fraud in the preparation of financial statements. This study aims to analyze the effect of internal control effectiveness and financial literacy on the tendency of accounting fraud in LPDs in Denpasar City. This research employs a quantitative approach with all LPDs operating in Denpasar City as the research objects. The research respondents consist of members of the LPD Supervisory Board, Heads of LPDs, and financial staff who have at least two years of work experience. Data from 93 respondents were collected through questionnaire distribution and analyzed using multiple linear regression after meeting the classical assumption tests. The results indicate that the effectiveness of internal control has a negative effect on the tendency of accounting fraud. The more effective the internal control implemented, the lower the tendency of accounting fraud in LPDs. Financial literacy also has a negative effect on the tendency of accounting fraud, indicating that the more frequently LPD managers receive financial literacy, the lower the tendency of accounting fraud. These findings emphasize the importance of strengthening internal control systems and improving the financial literacy of LPD managers as strategic efforts to reduce the risk of accounting fraud and strengthen the financial governance of LPDs in Denpasar City.